Characterization of temporal expression of immune genes in female locust challenged by fungal pathogen, Aspergillus sp. - Waqas, Muhammad Saad; Xu, Xiao; Zhang, Pengfei; Guo, Jin; Hu, Shaojing; You, Yinwei; Zhang, Long (Frontiers in Immunology, 2025)
IntroductionThe innate immune system provides defense against invading pathogens in insects and mammals. MethodsWe conducted transcriptomic analyses of the locust Locusta migratoria under Aspergillus oryzae infection to clarify temporal variation in its molecular immune response. ResultsWe found that fat body cells and hemocytes play different roles in the immune response of locusts to Aspergillus infection at different time points after inoculation, and melanization was the main process underlying the immune response of female locusts. Most pattern recognition receptors (PRR) genes were up-regulated in fat body cells and down-regulated in hemocytes from 24 h to 72 h after inoculation. This means that fat body cells, but not hemocytes, would be able to precisely recognize invading pathogens. Most serine protease inhibitors (SERPINs) genes and clip domain serine proteinase (CLIP) genes were up-regulated in fat body cells. However, most SERPINs were down-regulated in hemocytes, which indicated that serine proteinases may be inhibited to activate downstream reactions involving the prophenoloxidase (PPO), peroxidase (POD), and Toll pathways. Most lysozymes, PPOs, and peroxiredoxin (PRDX) are effectors that were up-regulated in fat body cells 24 h after inoculation but down-regulated 48 h and 72 h after inoculation. Similar patterns were observed for effectors in hemocytes, which indicates that locust immune genes expression was suppressed by A. oryzae 72 h after inoculation, and might result in the weak melanization of locusts in response to Aspergillus infection. DiscussionOur findings enhance our understanding of insect–fungi interactions, as well as have implications for the development of more effective microbial control strategies for the management of locust populations.